2018
DOI: 10.1080/13621718.2018.1473077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bonding interface between steel/steel and steel/Ni by ultrasonic welding

Abstract: Ultrasonic welding is a solid-state welding technique that can bond materials at a relatively low temperature and pressure. In this study, steel/steel and steel/Ni combinations were successfully bonded by ultrasonic welding, and the development of the bonding interface was examined. The bonding strength was obtained by a lap shear test and increased with welding time, as did the fraction of bonded area observed by SEM. The bonding process sequence was investigated by SEM and electron backscatter diffraction (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…As shown, contact areas with island shapes are distributed at the fractured surface and expanded along the oscillation direction, and their numbers increased with welding time. The fracture observations in S/S with increasing welding time also can be referred to our previous study [12], whereas the contact areas were examined by energy dispersive X-ray spectrometry; they exhibited Ni composition on the steel side and Fe composition on the Ni side, and vice versa.
Figure 3 Fractured surfaces of IF steel in the case of rough/smooth after (a) 0.01 s; (b) 0.25 s; (c) 2.0 s; and (d) 2.5 s.
…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…As shown, contact areas with island shapes are distributed at the fractured surface and expanded along the oscillation direction, and their numbers increased with welding time. The fracture observations in S/S with increasing welding time also can be referred to our previous study [12], whereas the contact areas were examined by energy dispersive X-ray spectrometry; they exhibited Ni composition on the steel side and Fe composition on the Ni side, and vice versa.
Figure 3 Fractured surfaces of IF steel in the case of rough/smooth after (a) 0.01 s; (b) 0.25 s; (c) 2.0 s; and (d) 2.5 s.
…”
Section: Resultsmentioning
confidence: 91%
“…At the fractured surfaces of R/S after 0.01 s of welding (Figure 3(a)), the contact areas in S/S [12] were smaller and more uniformly distributed than those in R/S. Further, the intervals of contact areas perpendicular to the oscillation direction in R/S were larger than those in S/S.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [8] confirmed that USW is a solid phase joining technique and that under the combination effects of high shear frequency vibration and clamping force, two metal sheets can be joined by such a technique. Daniels [9] noted that USW was first introduced for thin foils joining, wire bonding, and tube sealing in the 1950 s. It was used to join thicker metal sheets (such as Al, Cu, NiTi, Fe, and Ni) due to advancements in the welding system technique [10,11,12,13]. In comparison with friction stir spot welding and resistance spot welding, USW has low energy consumption (~0.6–1.5 kJ per weld), because the major heat generation is at the weld interface, not on the top surface of the specimen [14].…”
Section: Introductionmentioning
confidence: 99%